Implementasi Metode Multi Attribute Utility Theory (Maut) Pada Sistem Pendukung Keputusan Recruitment Barista Pada Arabica Cafe - Kusuma, Ade Ayunda; Ningsih, Trans (STMIK Budi Darma, 2024)
Arabica Cafe is a coffee shop that provides various types of coffee and drinks which have their own characteristics depending on the coffee maker or barista who makes the coffee. Based on interviews conducted with the owner of Arabica Cafe and several related parties, it was explained that the assessment of prospective baristas who apply is still based on individuals so that lack of accuracy in recruiting prospective baristas is considered to be an ongoing problem for cafe owners. therefore a decision support system (DSS) is needed which is expected to be able to help in resolving these problems. A Decision Support System (SPK) is a computerized system used to assist decision making in a company or organization. The decision support system as a solution in solving problems with the application and application of the Multi Attribute Utility Theory (MAUT) method which is able to provide maximum results to obtain superior barista recruitment is Fanny Sembiring in alternative A9 with a result of 0.80832 as the alternative chosen in the recruitment of baristas after going through the stages application of the method.